Representations of Ultra-Processed Foods: A Global Analysis of How Dietary Guidelines Refer to Levels of Food Processing - Daniela Koios; Priscila Machado; Jennifer Lacy-Nichols (Kerman University of Medical Sciences, 2022)
Background  As evidence grows about negative health impacts of ultra-processed foods (UPFs), nutrient-centred advice is contested, and food-based dietary guidelines are increasingly utilised. Previous analyses of dietary guidelines evaluated their potential impact on health and sustainability, but little research has been conducted to examine how the concept of UPFs is reflected in dietary advice for consumers. This paper systematically analyses whether and how UPFs are represented in dietary guidelines internationally.Methods  Based on a systematic online search, the consumer-targeted key messages of 106 dietary guidelines were identified and a qualitative content analysis was conducted. A coding framework was developed to classify messages as 'eat more' or 'eat less' according to the language used (eg, 'choose' vs 'avoid') and to differentiate between a focus on nutrients or food processing. Specific foods mentioned in 'eat less' guidelines were classified according to their level of processing using the NOVA framework.Results  99% of guidelines utilised some type of nutrient-based message, either promoting 'positive' nutrients (eg, vitamins) or discouraging the consumption of 'negative' nutrients (mainly salt, sugar and fat). Explicit references to food processing were present in 45% of 'eat less' guidelines and 5% of 'eat more' guidelines. Implicit references (eg, promoting 'raw' or discouraging 'packaged' foods) were found in 43% of 'eat less' and 75% of 'eat more' guidelines. 53% of the specific foods referred to in 'eat less' advice were UPFs.Conclusion  Overall, nutrient-based messages were more common than messages about processing levels. The majority of discouraged foods were UPFs, however some minimally processed foods were discouraged, which points to tensions and contradictions between nutrient- and processing-based dietary advice. As dietary guidelines begin to include advice about food processing, it is important to consider both consumer understanding of the terms used and their capacity to act on the advice.